CONTRACEPTIVE PRACTICES AND THE PREVENTION OF SEXUALLY-TRANSMITTED DISEASES AMONG NURSING ACADEMICS - Lillia Michely Nunes Abreu; Anamária Serra Tavares (Universidade Federal do Paraná, 2012)
This descriptive study with a quantitative approach aimed to investigate conduct and practices in contraception and the prevention of sexually-transmitted diseases among nursing academics, identify the methods of contraception used and to describe risky behaviors. The data was obtained via a questionnaire applied to 135 students between May and June 2011, and was analyzed by descriptive statistics with absolute frequency and percentages. The sample was mainly made up of single young women, aged between 20 and 23. The masculine condom and the oral contraceptive pill were the most-related methods, used separately or combined. Early initiation of sexual relations and practices without the use of condoms was noted, which resulted in 5,9% of the students having contracted a sexually-transmitted disease. It was observed that nursing academics' conduct, where contraception and prevention of sexually-transmitted diseases are concerned, is precarious.